Drug Interactions of Thalidomide with Midazolam and Cyclosporine A: Heterotropic Cooperativity of Human Cytochrome P450 3A5 - Okada, Yusuke (American Society for Pharmacology and Experimental Therapeutics, 2009)
There is growing clinical interest of thalidomide because of its immunomodulatory and antiangiogenic properties, despite its teratogenicity. However, little information about thalidomide has been reported regarding its precise effects on drug-metabolizing enzymes. We investigated the effects of thalidomide on cytochrome P450 (P450) enzymes in human liver microsomes to clarify the potential for possible drug interactions. Thalidomide inhibited S-mephenytoin 4′-hydroxylation activities of recombinant P450 2C19 and human liver microsomes: the apparent concentration of thalidomide producing 50% inhibition was approximately 270 μM for P450 2C19. Midazolam 4-hydroxylation activities were suppressed by thalidomide, but activities of 1′-hydroxylation and total midazolam oxidation and testosterone 6β-hydroxylation were enhanced in the presence of thalidomide. Recombinant P450 3A5 was found to have altered kinetics at clinically relevant concentrations of thalidomide (10–30 μM). P450 3A4 was also affected, but only at higher thalidomide concentrations. Enhanced midazolam hydroxylation by thalidomide was also seen in liver microsomal samples harboring the CYP3A5*1 allele. Similarly enhanced rates of cyclosporine A clearance were observed in P450 3A5 and liver microsomes expressing P450 3A5 in the presence of thalidomide. A proposed effector constant for thalidomide corresponded roughly to its clinical plasma levels. Docking studies with a P450 3A5 homology model, based on the published structure of P450 3A4, revealed close interaction between thalidomide and the heme of P450 3A5. The present results suggest that total midazolam metabolism or cyclosporine A clearance may be increased by thalidomide in a dose-dependent manner. Unexpected drug interactions involving thalidomide might occur via heterotropic cooperativity of polymorphic P450 3A5.